2005
DOI: 10.1111/j.1365-2036.2005.02534.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of esomeprazole and lansoprazole for control of intragastric pH in patients with symptoms of gastro‐oesophageal reflux disease

Abstract: SUMMARYBackground: Intragastric acid suppression is the most direct measure of the pharmacodynamic efficacy of proton pump inhibitors, which are the most effective drugs for acid-related diseases. Aim: To compare the effectiveness of once and twice daily dosing of lansoprazole and esomeprazole in controlling intragastric acidity (target gastric pH > 4.0) over a 24-hour period. Methods:In an open-label, two-way crossover study, 45 Helicobacter pylori-negative patients with gastro-oesophageal reflux disease were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…All patients reported heartburn, regurgitation, absence of dysphagia and symptom-relief upon treatment with proton pump inhibitor (esomeprazole 40 mg twice daily for at least 2 weeks) [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients reported heartburn, regurgitation, absence of dysphagia and symptom-relief upon treatment with proton pump inhibitor (esomeprazole 40 mg twice daily for at least 2 weeks) [20].…”
Section: Resultsmentioning
confidence: 99%
“…Demographic data of patients are depicted in Table 2. In keeping with recommendations published by the American Gastroenterological Association (AGA) [19], all patients were on proton pump inhibitor (PPI) treatment for at least 2 weeks prior to endoscopy (2 x 40 mg esomeprazole daily) [20] for exclusion of inflammatory changes impairing histopathologic diagnosis [7,8,19].…”
Section: Study Protocolmentioning
confidence: 99%
“…Data from many studies indicate that the likelihood of esophagitis healing relates directly to the potency of drug antisecretory effect [32][33][34][35]. Hence, a high healing rate has been consistently reported after 4 and 8 weeks standard dose PPI regimen [7].…”
Section: Healing Of Reflux Esophagitismentioning
confidence: 99%
“…iv) Proton pump inhibitors Overview: PPIs are generally accepted to be significantly more effective than placebo, H 2 -RAs and prokinetics for heartburn relief and general improvement of symptoms in patients without documented erosive esophagitis. Virtually all clinical data are derived from studies using a once-daily PPI and, although there are gastric pH data to show that twice-daily PPIs produce greater acid suppression than oncedaily therapy in patients with GERD symptoms, 27 there are no clinical data on high-dose PPI therapy in this patient group. Heartburn relief with standard dose omeprazole (20 mg daily) was greater than with half-dose omeprazole (10 mg daily) but previous studies have reported no differences between distinct doses of esomeprazole (40 mg and 20 mg) or between esomeprazole (40 mg daily) and omeprazole (20 mg daily).…”
Section: Diet and Lifestyle Changesmentioning
confidence: 99%